A high-performance composite yarn based on acetate filament and preparation method thereof

By twisting the acetate filament on the modified collagen nylon nylon, the problem of low the strength of the acetic acid fiber and insufficient hygroscopic absorption have been solved, the preparation of high -performance composite gauze, expanded its application scenarios and improved wearing it. Comfort.

CN118704130BActive Publication Date: 2025-01-24广东粤新纺织科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410803354.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-01-24
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

The low strength of acetate fiber (CA fiber) limits its application range, and its reduced hydrophilicity and insufficient hygroscopicity affect its wearable comfort and application scenarios in textiles.

Method used

Adopt a dual -share twisting structure, twist 2 to 3 acetic acid filaments on the collagen nylon long wire, and the combination of collagen nylum filament loaded by alcohol and nano oxide is improved. The mechanical properties and moisture absorption performance of the acetic acid filament.

Benefits of technology

It improves the fracture strength and elongation of acetic acid long wires, expand its application scenario, and improve its wearing comfort and hygroscopic performance in textiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118704130B_ABST
    Figure CN118704130B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-performance composite yarn based on acetate filaments, wherein the composite yarn adopts a double-twisted structure, and the composite yarn is 2 to 3 strands of acetate filaments twisted in the same direction on collagen nylon filaments. The present invention combines acetate filaments and collagen nylon filaments by twisting, and improves the disadvantages of low strength of acetate filaments by using collagen nylon filaments, while making the product have all the advantages of both raw materials. On the other hand, the same-direction twisting method adopted has higher breaking strength and breaking elongation in mechanical properties, which effectively expands the application scenarios of acetate filaments.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of patent number "202311194075.3", application date "2023-09-15", and name "A composite yarn based on acetate filament and collagen nylon filament and its preparation method". Technical Field

[0002] The invention belongs to the technical field of spinning, and in particular relates to a high-performance composite yarn based on acetate filaments and a preparation method thereof. Background Art

[0003] Acetate fiber (CA fiber) has a wide range of uses. It can be used to make cigarette filters, textiles, liquid crystal displays (LCDs), film bases, etc. Among them, the manufacture of cigarette filters is its most extensive use. About 80% of the world's CA is used to produce cigarette filters, and the rest can be used in textiles and other fields.

[0004] CA fiber has a weakness, its strength is quite low, which adds a lot of difficulty to spinning, and the products made of CA fiber cannot be used in fields with special requirements for strength. In addition, since CA is obtained by replacing the hydroxyl groups on cellulose with acetyl groups, the hydrophilicity of CA is significantly lower than that of cellulose. Therefore, when it is used as a fabric for clothing, its wearing comfort is also reduced. In addition, the low hygroscopicity of CA also affects its application to a certain extent. For example, fibers with low hygroscopicity are not suitable for the fabrics of summer close-fitting clothing.

[0005] The characteristics of CA greatly affect its application scenarios and there are many limitations. Summary of the invention

[0006] The purpose of the present invention is to solve the above-mentioned technical problems and provide a high-performance composite yarn based on acetate filaments and a preparation method thereof.

[0007] In order to solve the above problems, the present invention is implemented according to the following technical solutions:

[0008] In a first aspect, the present invention provides a high-performance composite yarn based on acetate filaments, wherein the composite yarn adopts a double-twisted structure, and the composite yarn is 2 to 3 strands of acetate filaments twisted in the same direction on collagen nylon filaments.

[0009] In combination with the first aspect, the present invention further provides a first preferred implementation of the first aspect, specifically, the acetate filaments are acetate filaments modified by alcoholysis, and the alcoholysis modification comprises the following steps:

[0010] Use anhydrous ethanol as a solvent to prepare a 0.5 mol / L sodium hydroxide alcohol solution as an alcoholysis solution;

[0011] Immerse the acetate filament in the alcoholysis solution, take out the acetate filament after 1 hour at room temperature, and wash the alcoholysis acetate filament with deionized water for 2 to 3 times, each time for 10 minutes;

[0012] After cleaning, the alcoholyzed acetate filaments are placed at room temperature to dry.

[0013] In combination with the first aspect, the present invention further provides a second preferred implementation of the first aspect. Specifically, the method for preparing the acetate filament further includes the following steps:

[0014] A mixed solution of 90% acetone and 10% N,N-dimethylacetamide is prepared, and the mixed solution is used as a solvent to prepare a CA spinning solution with a mass fraction of 20%;

[0015] Add 3% by mass of cellulose nanocrystals into the CA spinning solution and stir well;

[0016] Acetate filaments were obtained by wet spinning, wherein a wet spinning machine was used for spinning, and the spinning process parameters were as follows: drafting roller 2.00 m / min, first roller 2.00 m / min, second roller 2.00 m / min, traverse 2 times / min, winding 1.80 m / min, and spinning was performed at room temperature.

[0017] In combination with the first aspect, the present invention further provides a third preferred implementation of the first aspect, specifically, the collagen nylon filament is loaded with nano zinc oxide.

[0018] In combination with the first aspect, the present invention further provides a fourth preferred implementation of the first aspect. Specifically, the method for preparing the collagen nylon filament comprises the following steps:

[0019] A masterbatch adding device is used to feed collagen masterbatch, nano zinc oxide and polyamide 6 glossy slices into a screw extruder after being metered by a metering feeder, and mixed and extruded after being fully melted; the mass fraction of collagen masterbatch is 7%, and the mass fraction of nano zinc oxide is 6%;

[0020] The melt is accurately metered by a metering pump and enters the spinning assembly, where it is ejected through a spinneret to form a filament bundle.

[0021] In combination with the first aspect, the present invention further provides a fifth preferred implementation of the first aspect, specifically, the linear density of the acetate filament is 82.5 dtex, and the linear density of the collagen nylon filament is 76.78 dtex.

[0022] In a second aspect, the present invention further provides a method for preparing a high-performance composite yarn based on acetate filaments according to the first aspect, the preparation method comprising the following steps:

[0023] A yarn twisting machine is used to twist 2 to 3 strands of acetate filaments in the same direction on the collagen nylon filaments;

[0024] Among them, the re-twisting spindle speed in the twisting process is set to 500r / min, and the twisting twist is 150 twists / 10cm.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The invention provides a high-performance composite yarn based on acetate filaments. The composite yarn adopts a double-strand twisting structure. The composite yarn is composed of 2 to 3 strands of acetate filaments twisted in the same direction on collagen nylon filaments.

[0027] The present invention combines acetate filaments and collagen nylon filaments by twisting, and improves the disadvantages of low strength of acetate filaments by using collagen nylon filaments, while making the product have all the advantages of both raw materials. On the other hand, the same-direction twisting method is adopted, and its mechanical properties have higher breaking strength and breaking elongation, which effectively expands the application scenarios of acetate filaments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings, wherein:

[0029] Figure 1 It is a schematic structural diagram of a high-performance composite yarn based on acetate filaments of the present invention, in which three acetate filaments are twisted in the same direction on collagen nylon filaments;

[0030] In the figure:

[0031] 1,2,3-acetate filaments;

[0032] 4-Collagen nylon filament. DETAILED DESCRIPTION

[0033] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] like Figure 1 As shown, a preferred structure of a high-performance composite yarn based on acetate filaments according to the present invention.

[0035] In the present invention, the high-performance composite yarn based on acetate filaments adopts a double-twisted structure, and the composite yarn is 2 to 3 strands of acetate filaments twisted in the same direction on collagen nylon filaments.

[0036] The present invention combines acetate filaments and collagen nylon filaments by twisting, and improves the disadvantages of low strength of acetate filaments by using collagen nylon filaments, while making the product have all the advantages of both raw materials. On the other hand, the same-direction twisting method is adopted, and its mechanical properties have higher breaking strength and breaking elongation, which effectively expands the application scenarios of acetate filaments.

[0037] 1. Acetate filaments of the present invention

[0038] Acetate filament is similar to real silk among chemical fibers, with elegant luster, bright coloring, strong color fastness, soft and smooth feel, light texture, low moisture regain, good elasticity, not easy to wrinkle, good drape, thermoplasticity, and dimensional stability. Characteristics of acetate filament:

[0039] 1. Good thermoplasticity: Acetate fiber softens at 200℃~230℃ and melts at 260℃. This feature makes acetate fiber thermoplastic and similar to synthetic fiber. After plastic deformation, the shape will not return, and the deformation is permanent. Fabrics woven with acetate filaments have good formability, can beautify the human body curve, and are generous and elegant overall.

[0040] 2. Excellent dyeability: Acetate fibers can usually be dyed with disperse dyes, and have good coloring properties and bright colors, which are better than other cellulose fibers. Acetate fabrics have good thermoplasticity. Acetate fibers soften at 200℃~230℃ and melt at 260℃. Similar to synthetic fibers, they will not recover their shape after plastic deformation, and have permanent deformation.

[0041] 3. Appearance similar to mulberry silk: The appearance and gloss of acetate fiber are similar to mulberry silk, and the soft and smooth feel is also similar to mulberry silk. Its specific gravity is the same as mulberry silk, so the drape is no different from mulberry silk. Fabrics woven from acetate filaments are easy to wash and dry, and are not moldy or moth-eaten. Acetate fabrics have better elasticity than viscose fibers.

[0042] 4. Performance close to mulberry silk: Compared with the physical and mechanical properties of viscose fiber and mulberry silk, acetate fiber has lower strength, larger elongation at break, lower ratio of wet strength to dry strength, but higher than viscose, smaller initial modulus, lower regain than viscose fiber and mulberry silk, but higher than synthetic fiber, and its ratio of wet strength to dry strength, relative hook strength and knotting strength, elastic recovery rate, etc. are not much different from mulberry silk. Therefore, acetate fiber is closest to mulberry silk in performance among chemical fibers.

[0043] 5. Acetate fabrics are not charged and do not easily absorb dust in the air. They can be dry cleaned, washed in water, or hand washed at temperatures below 40°C. They overcome the weaknesses of silk and wool fabrics that are often bacterial and dusty and can only be dry cleaned. They also do not have the disadvantage of wool fabrics that are easily eaten by insects. They are easy to care for and store. In addition, acetate fabrics have the resilience and smooth feel of wool fabrics.

[0044] In a preferred implementation, the method for preparing the acetate filament further comprises the following steps:

[0045] Step S1: preparing a mixed solution of 90% by mass acetone and 10% by mass N,N-dimethylacetamide, and using the mixed solution as a solvent to prepare a CA spinning solution with a mass fraction of 20%;

[0046] Step S2: adding 3% by mass of cellulose nanocrystals to the CA spinning solution and stirring the solution thoroughly.

[0047] In a specific implementation, a homogenizer is used for high-speed stirring, with a stirring time of 30 minutes and a rotation speed of 30,000 rpm, so that the cellulose nanocrystals can be evenly dispersed in the CA spinning solution. The CA spinning solution is then placed in an ultrasonic cleaner and continuously ultrasonicated for standby use.

[0048] Step S3: Acetate filaments are prepared by wet spinning, wherein a wet spinning machine is used for spinning, and the spinning process parameters are set as follows: drafting roller 2.00 m / min, first roller 2.00 m / min, second roller 2.00 m / min, traverse 2 times / min, winding 1.80 m / min, and spinning is carried out at room temperature.

[0049] The present invention adds cellulose nanocrystals to CA spinning solution to reinforce acetate filaments. Cellulose nanocrystals (CNC) are a nanoscale substance extracted from natural fiber cellulose such as wood, cotton, straw, reed, hemp and bagasse. They not only have the characteristics of nanoparticles, but also have the characteristics of high orientation, high strength, high elastic modulus, large aspect ratio, etc., and can be completely degraded, and serve as a reinforcing material with excellent performance in CA fibers.

[0050] Product testing of acetate filaments

[0051] (1) X-ray diffraction (XRD) analysis: X-ray diffractometer was used to analyze the crystal structure of CNC. The scanning angle range was 10-90° and the scanning speed was 5° / min.

[0052] Through analysis, it was found that the cellulose nanocrystals in the acetate filaments were the crystalline structure of cellulose II.

[0053] (2) Scanning electron microscopy (SEM) analysis: Field emission scanning electron microscopy was used to observe the morphology of acetate filaments. The SEM parameters were set as follows: gold spraying time 240s, working voltage 10kV. The changes in fiber diameter and morphology at different cellulose nanocrystal concentrations (0%, 1%, 3%, 5%) were compared.

[0054] Through analysis, it was found that as the concentration of cellulose nanocrystals increased, the diameter distribution of acetate filaments gradually widened: the diameter distribution of 0% doped acetate filaments was between 150 and 350nm; when the concentration of cellulose nanocrystals increased to 1% or 3%, the diameter distribution of acetate filament fibers was between 150 and 400nm, with little difference. When the concentration of cellulose nanocrystals increased to 5%, the diameter distribution range of acetate filament composite fibers gradually increased to 150-950nm. The reason for the widening of fiber distribution is the poor dispersibility of cellulose nanocrystal reinforcement, which gradually deteriorates with the increase of its concentration, resulting in poor uniformity of acetate filaments, thus presenting a wider diameter distribution.

[0055] On the other hand, with the increase of cellulose nanocrystal concentration, the average diameter of acetate filaments gradually increased, and the viscosity of spinning solution increased, so the fiber diameter showed a trend of increasing.

[0056] (3) The mechanical properties of the fiber samples were tested using an electronic single yarn strength tester. The linear density of each fiber sample was measured before the test, and the required pre-tension of the sample was calculated based on the measured linear density at (0.5±0.1) cN / tex. The instrument parameters were set as follows: clamping distance, 100 mm; stretching rate, 100 mm / min; temperature, 20°C; humidity, 65%.

[0057] The experiment found that with the increase of the concentration of cellulose nanocrystals, the breaking stress and breaking elongation of acetate filaments both increased first and then decreased, as shown in the following table.

[0058]

[0059] In a preferred embodiment, the acetate filaments used in the present invention are acetate filaments modified by alcoholysis.

[0060] Through alcoholysis modification, the surface of acetate filament fiber becomes denser after alcoholysis, and the mechanical properties of acetate filament are comprehensively improved by synergistic CNC doping. On the other hand, by combining acetate filament and collagen nylon filament by twisting, three combined technical means are used to synergistically improve the shortcomings of acetate filament such as low strength, while making the product have all the advantages of both raw materials, greatly expanding the application scenarios of acetate filament.

[0061] In a specific implementation, the present invention also provides an implementation method of alcoholysis modification, comprising the following steps:

[0062] Step S1: using anhydrous ethanol as a solvent to prepare a 0.5 mol / L sodium hydroxide alcohol solution as an alcoholysis solution for standby use;

[0063] Step S2: immersing the acetate filaments in the alcoholysis solution, taking out the acetate filaments after 1 hour at room temperature, and washing the alcoholysis acetate filaments with deionized water for 2 to 3 times, each time for 10 minutes;

[0064] Step S3: After washing, the alcoholysate acetate filaments are placed at room temperature to dry.

[0065] The surface of acetate filaments becomes denser after alcoholysis, and the mechanical properties are improved to a certain extent compared with the acetate filaments before modification. Alcoholysis acetate filaments have moisture absorption properties comparable to viscose and bamboo fiber and better moisture release properties, which can improve wearing comfort and can be used in the field of textiles and clothing.

[0066] After testing, the mechanical properties of the product have changed as follows:

[0067]

[0068] The breaking strength of the fiber is slightly improved before and after alcoholysis, and the breaking strength of the acetate filament obtained after alcoholysis is increased. This is because the acetyl group is detached, the molecular chain has better regularity, and the hydrogen bond content in the molecule is increased, which increases the strength.

[0069] On the other hand, the wet strength of acetate filaments is significantly lower than that of dry strength. However, the elongation at break of acetate filaments in wet state is significantly increased, about 1.3 times that of CA fibers; in addition, the elongation at break of acetate filaments in wet state is 1.7 times that in dry state. Therefore, in general, the mechanical properties of the fibers obtained after alcoholysis are improved to a certain extent.

[0070] On the other hand, since the acetyl groups on the acetate filaments after alcoholysis are replaced by hydrophilic hydroxyl groups, the moisture absorption and release of the fibers will also be affected. The moisture absorption and release of the fibers before and after alcoholysis were tested. The moisture absorption and release properties of two other cellulose fibers (viscose and bamboo fibers) were selected as controls.

[0071] Viscose has the best moisture absorption performance, with a moisture regain of about 8%. Bamboo fiber ranks second with a moisture regain of about 7.5%. The moisture regain of acetate filament after alcoholysis is slightly lower than that of viscose and bamboo fiber, about 7%, while the moisture regain of acetate filament is significantly lower than that of the other three cellulose samples, only about 3.3%. The moisture absorption rates of the four samples are also different. The moisture absorption rates of viscose and bamboo fiber are slightly faster than those of acetate filament after alcoholysis, but the moisture absorption rates of the three samples are significantly higher than those of acetate filament.

[0072] On the one hand, the moisture release performance of the acetate filament after alcoholysis is the best, and the moisture content is reduced the most, reaching about 1.8%, followed by viscose, which is about 1.5%, followed by bamboo fiber, which is about 1.2%, and the moisture content of the worst acetate filament is reduced by only about 1.0%. The moisture release rate of the acetate filament after alcoholysis is obviously better than the other three samples, and the moisture release rate of bamboo fiber and acetate filament is close, while viscose is only slightly faster than these two samples. Therefore, the present invention obtains a regenerated cellulose fiber that is close to viscose and bamboo fiber in hygroscopicity and slightly better than the two fibers in moisture release performance through the acetate filament after alcoholysis.

[0073] By selecting the specific acetate filaments of the present invention, the composite yarn can be endowed with excellent mechanical properties and hygroscopic properties, and the prepared fabrics, clothing, etc. can more easily absorb sweat discharged from the human body, and at the same time can discharge the moisture absorbed by the sweat more quickly, thereby making the human body feel comfortable; it is suitable for preparing summer clothing or functional clothing.

[0074] 2. Collagen nylon filament of the present invention

[0075] Collagen nylon fiber is a new type of textile material for the development of clothing textiles. The transverse cross-section of the fiber is an irregular circle, and there are raised particles on the longitudinal surface.

[0076] In a specific implementation, the collagen nylon filaments used in the present invention are loaded with nano zinc oxide.

[0077] Furthermore, the present invention also provides a method for preparing the collagen nylon filament, which specifically comprises the following steps:

[0078] Step S1: using a masterbatch adding device, feeding collagen masterbatch, nano zinc oxide and polyamide 6 glossy slices into a screw extruder after being metered by a metering feeder, and mixing and extruding after being fully melted; the mass fraction of the collagen masterbatch is 7%, and the mass fraction of the nano zinc oxide is 6%;

[0079] In one implementation, the temperatures of the screw zones and the box during the melting process are 256, 258, 260, 262, 263 and 263° C., respectively.

[0080] Step S2: The melt is accurately metered by a metering pump and enters the spinning assembly, and is ejected through a spinneret to form a filament bundle.

[0081] In one implementation, the number of spinneret holes on the spinneret in step S2 is 24; the filament bundles sucked by the monomer are cooled by side blowing, the cooling temperature is 23°C, the humidity is 85%, and the wind speed is 0.53 m / s; the fibers cooled by side blowing are accurately metered and oiled and bundled through an oil nozzle, and the concentration of the oil used is 6%; the filament bundles after oiling are passed through a pre-network device and a guide wire disk and are wound into shape, and the production speed is 4300 m / min, to obtain collagen nylon filaments.

[0082] Product test of collagen nylon filament

[0083] (1) Tested in accordance with GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method". The standard stipulates that for general samples, if the antibacterial rate of Escherichia coli is ≥70%, the antibacterial rate of Staphylococcus aureus is ≥70%, and the antibacterial rate of Candida albicans is ≥60%, then the sample has antibacterial properties.

[0084] After testing, the antibacterial rates of collagen nylon filaments with added nano zinc oxide against Escherichia coli, Staphylococcus aureus and Candida albicans all reached the national standard judgment values, indicating that collagen nylon filaments have antibacterial properties.

[0085] (2) Tested in accordance with GB / T35263-2017 "Testing and Evaluation of Instantaneous Cooling Properties of Textiles". The standard stipulates that for general samples, the contact cooling coefficient of the test should not be less than 0.15 J / (cm·s), and the sample has cooling properties.

[0086] According to the test, the contact coolness coefficient of the collagen nylon filament obtained by melt spinning is 0.32 J / (cm·s), which reaches the national standard judgment value, indicating that the collagen nylon filament has cool properties.

[0087] (3) Tensile performance test: The test was conducted using a YG023B-III single yarn strength tester in accordance with GB / T14344-2008 “Test method for tensile properties of chemical filaments”.

[0088]

[0089] The experiment found that the addition of collagen masterbatch reduced the breaking strength of collagen nylon filaments to varying degrees. There was a difference in compatibility between a small amount of inorganic powder and the melt, which resulted in shear stress at the boundary between the two phases and caused fiber breakage. When the amount of masterbatch added increased from 5% to 7%, the breaking strength of collagen nylon filaments increased slightly. With the increase of inorganic powder, it became partially compatible with the melt to a certain extent, enhancing the chain connection and preventing the fiber from breaking during the drawing process.

[0090] The present invention also provides a method for preparing high-performance composite yarn based on acetate filaments, the preparation method comprising the following steps:

[0091] A yarn twisting machine is used to twist 2 to 3 strands of acetate filaments in the same direction on the collagen nylon filaments;

[0092] The re-twisting spindle speed in the twisting process is set to 500 r / min, and the twisting twist is 150 twists / 10 cm. The linear density of the acetate filament is 82.5 dtex, and the linear density of the collagen nylon filament is 76.78 dtex.

[0093] The present invention combines acetate filaments and collagen nylon filaments by twisting, and improves the disadvantages of low strength of acetate filaments by using collagen nylon filaments, while making the product have all the advantages of both raw materials. On the other hand, the same-direction twisting method is adopted, and its mechanical properties have higher breaking strength and breaking elongation, which effectively expands the application scenarios of acetate filaments.

[0094]

[0095] For other structures of the high-performance composite yarn based on acetate filaments and the preparation method thereof described in this embodiment, refer to the prior art.

[0096] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A high-performance composite yarn based on acetate filaments, characterized in that: The composite yarn is composed of 2 to 3 strands of acetate filaments twisted in the same direction on a collagen nylon filament core yarn, and the composite yarn has a breaking strength of 6.21 cN / tex and a breaking elongation of 60.32%; The linear density of the acetate filament is 82.5 dtex, and the linear density of the collagen nylon filament is 76.78 dtex; The acetate filaments are acetate filaments modified by alcoholysis, the diameter of the acetate filaments is distributed between 150 and 400 nm, the acetate filaments soften at 200° C. to 230° C., and melt at 260° C. The acetate filaments have a breaking strength of 7.53 cN / tex and a breaking elongation of 30.58% in a dry state, and a breaking strength of 5.52 cN / tex and a breaking elongation of 54.58% in a wet state; the preparation method of the acetate filaments further comprises the following steps: A mixed solution of 90% by mass acetone and 10% by mass N,N-dimethylacetamide was prepared, and the mixed solution was used as a solvent to prepare a CA spinning solution with a mass fraction of 20%; Add 3% by mass of cellulose nanocrystals to the CA spinning solution and stir it evenly. Specifically, use a homogenizer to stir at high speed for 30 minutes at a speed of 30,000 rpm. Then place the CA spinning solution in an ultrasonic cleaner and continue ultrasonication for later use. Acetate filaments were prepared by wet spinning, wherein a wet spinning machine was used for spinning, and the process parameters set for spinning were: drafting roller 2.00 m / min, first roller 2.00 m / min, second roller 2.00 m / min, traverse 2 times / min, winding 1.80 m / min, and spinning was carried out at room temperature; Among them, the cellulose nanocrystals in the acetate filaments are the crystal structure of cellulose II; The collagen nylon filament is loaded with nano zinc oxide, the breaking strength of the collagen nylon filament is 6.75 cN / tex, and the breaking elongation is 65.38%. The preparation method of the collagen nylon filament comprises the following steps: A masterbatch adding device was used to feed collagen masterbatch, nano zinc oxide and polyamide 6 glossy slices into a screw extruder after being metered by a metering feeder, and mixed and extruded after being fully melted; the mass fraction of collagen masterbatch was 7%, and the mass fraction of nano zinc oxide was 6%; during the melting process, the temperatures of the screw zones and the box body were 256, 258, 260, 262, 263 and 263°C respectively; The melt enters the spinning assembly after being accurately metered by a metering pump and is ejected through a spinneret to form a filament bundle; the number of spinneret holes on the spinneret is 24; the filament bundle sucked by the monomer is cooled by side blowing, the cooling temperature is 23°C, the humidity is 85%, and the wind speed is 0.53m / s.

2. A high-performance composite yarn based on acetate filament according to claim 1, characterized in that: The alcoholysis modification comprises the following steps: Use anhydrous ethanol as a solvent to prepare a 0.5 mol / L sodium hydroxide alcohol solution as an alcoholysis solution; Immerse the acetate filament in the alcoholysis solution, take out the acetate filament after 1 hour at room temperature, and wash the alcoholysis acetate filament with deionized water for 2 to 3 times, each time for 10 minutes; After cleaning, the alcoholyzed acetate filaments are placed at room temperature to dry.

3. The method for preparing a high-performance composite yarn based on acetate filament according to claim 1, characterized in that: The preparation method comprises the following steps: A yarn twisting machine is used to twist 2 to 3 strands of acetate filaments in the same direction on the collagen nylon filament core yarn; Among them, the re-twisting spindle speed in the twisting process is set to 500r / min, and the twisting twist is 150 twists / 10cm.

Citation Information

Patent Citations

  • Blended yarn of chinlon, acrylic fiber and cellulose acetate

    CN102839470A

  • Composite yarn textile capable of absorbing moisture and sensing cold and application thereof

    CN103132206A